Fermented Golden Apple Snail (Pomacea canaliculata L.) as Nutrient Solu-tion on the Growth of Batavia Lettuce (Lactuca sativa L.) under Kratky Hy-droponic Method - Borja, Norilie Jann A.; Bacani, Mary Rhovian B.; Coloma, Jiven F.; Esconde, Alyanna Mariko (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Golden apple snail (Pomacea canaliculata L.) is considered as a notorious pest in the rice fields along with different agricultural countries including the Philippines. This study was conducted to develop a fermented golden apple snail (FGAS) nutrient solution and investigate its effects on the growth of green loose-leaf Batavia lettuce (Lactuca sativa L.) under a Kratky hydroponic method. Green-loose leaf in grand rapid variety were used as the test plant to assess the effectiveness of the five treatments in the study: T1-SNAP solution, T2-FGAS, T3-double strength FGAS, T4-molasses, and T5-water. Due to its better suitability for trials carried out inside a screenhouse system, complete randomized design was used in the study. Moreover, the pH, electric conductivity (EC) and temperature of the treatments were measured as well as relative humidity and temperature within the screenhouse as indicators of its physicochemical characteristics. The developed FGAS has a 1:1:1 ratio composed of the meat of the P. canaliculata, food-grade molasses, and water. The result indicated that the lettuces which grew on T2-FGAS are comparable with the lettuces on the positive control. T1-SNAP solution in terms of plant height, number of leaves, length and width of the biggest leaf, fresh weight, and root length. However, lettuces on T2-FGAS displayed better leaf coloration, dry weight, and width of the biggest lettuce leaf than T1-SNAP. Additionally, L. sativa plants cultivated in T3-double strength FGAS produced results that were comparable to those obtained with negative treatments T4-molasses and T5-water. The study further revealed that the developed FGAS can probably be used as hydroponic nutrient solution by plant growers. The researchers recommend microbiological water analysis and lettuce contents analysis for further study.